Analysing Huawei’s International Trade Strategy and Response to Challenges - Li, Chenghao (Transactions on Economics, Business and Management Research, 2024)
This article extensively examines the variables that have contributed to Huawei’s remarkable achievements in international commerce, including the increasingly intricate global trade landscape and the significant influence of American trade restrictions and sanctions. This research thoroughly examines Huawei’s tactics and responses by employing a case study and analysis methodology. Moreover, it demonstrates that the corporation has accomplished its success through a wide array of measures. It involves more than simply expanding the global market and supply chain; it also entails making strategic expenditures in product research and development and significantly enhancing international strategic collaborations. The results of this study offer significant insights and can inspire other businesses dealing with similar trade hurdles and sanctions. It offers them useful assistance and reference in their efforts to overcome these problems and attain success in the global market, allowing them to learn from Huawei’s successful experiences and implement them in their own enterprises.